Repositioning technical and vocational education and training in Africa for global competitiveness: a bilingual model - Sulaimon Adewale (Universitas Kanjuruhan Malang, 2023)
This paper aims to reposition technical and vocational education and training in Africa by modelling the Chinese and Asian Tigers’ bilingual approach. This study used inductive content analysis cum transformative paradigm to identify relevant points constituting the major component of this conceptual paper. In addition, thematic method was also used to organize the identified points into categories and sub-categories. The introduction of the bilingualism approach to TVET programs following eight key stages will be actualised. Researchers are encouraged to conduct experimental empirical studies on Bilingualism in African TVET institutions, and its programs exploring the six stages conceptualised. Adding bilingualism to the TVET program will increase enrollment, make the program easier to get into, and help African countries’ economies grow. A bilingual policy will help many local talents who cannot speak other languages.